MORTALIDADE DE BLATTELLA GERMANICA (L.) (BLATTODEA: BLATTELLIDAE) EM FUNÇÃO DA PORCENTAGEM DE EXPOSIÇÃO AOS INSETICIDAS E DO TIPO DE SUPERFÍCIE, ANTES E APÓS A LAVAGEM - Silva, I.c. [UNESP]; Ferreira, M.c. [UNESP]; Parreira, R.s. [UNESP]; Martinelli, N.m. [UNESP]; Pazini, W.c. [UNESP] (Instituto Biológico, 2020)
Among the species of synanthropic cockroaches, the German cockroach, Blattella germanica (L., 1767) is the most important in terms of developing high populations in habitations. This study evaluated the mortality of B. germanica exposed to different areas treated with an equivalent amount of insecticides to verify the mortality caused by pesticides on smooth and rough surfaces, before and after washing. The experiments were carried out at the Departamento de Fitossanidade, UNESP/FCAV, Campus Jaboticabal, SP, Brazil. In the first experiment, the insecticide was applied to Petri dishes, with areas of exposure to the insecticide of 25, 50, 75 and 100%. The second application was performed by pressurized spraying on smooth and rough surfaces, which were then washed with detergent and water after treatment. The insecticides used were cypermethrin (Cynoff 400 AM) 2.5 c.p. g/L, deltamethrin (250 Deltagard WG) 1.0 c.p. g/L; lambda-cyhalothrin (Icon 5 EC) c.p. 5.0 mL/L and an untreated plot (control). In the first experiment, 5 adult insects were enclosed for fifteen minutes, while 10 were enclosed in the second experiment. Mortality evaluations were performed at 0, 1, 2, 4, 24, 48 and 72 hours after confinement. It was found that the insecticides used in 50%, 75% and 100% of the area resulted in a high mortality of B. germanica. The insecticides cypermethrin, deltamethrin and lambda-cyhalothrin proved efficient for the control of B. germanica, before the washing of the smooth surface. The effectiveness of these insecticides was greater on a smooth surface than a rough one. After washing, the effectiveness was lower for both surfaces.

Entre as espécies sinantrópicas de baratas, a barata alemã, Blattella germanica (L., 1767), é a mais importante por desenvolver altas populações em habitações. Este trabalho objetivou avaliar a mortalidade de B. germanica exposta a diferentes áreas tratadas, com quantidade equivalente de inseticidas e verificar a mortalidade provocada por inseticidas em superfícies lisa e rugosa, antes e após lavagem. Os experimentos foram conduzidos no Departamento de Fitossanidade da UNESP/FCAV de Jaboticabal, SP. No primeiro experimento, a aplicação dos inseticidas foi realizada sobre placas de Petri, com áreas de exposição ao inseticida de 25, 50, 75 e 100%. No segundo, a aplicação foi realizada com pulverizador costal pressurizado, sobre superfícies lisa (de azulejo) e rugosa (de cimento), que posteriormente foram lavadas com detergente e água corrente. Foram utilizados os inseticidas cypermethrin (Cynoff 400 PM) 2,5 g p.c./L; deltamethrin (Deltagard WG 250) 1,0 g p.c./L; lambda-cyhalothrin (Icon 5 CE) 5,0 mL p.c./L e uma testemunha sem aplicação. Foram confinadas, por quinze minutos, cinco baratas adultas no primeiro experimento e dez no segundo. As avaliações de mortalidade foram realizadas 0, 1, 2, 4, 24, 48 e 72 horas após o confinamento. Assim, conclui-se que os inseticidas aplicados em 50%, 75% e 100% das áreas resultaram em alta mortalidade de B. germanica. Os inseticidas cypermethrin , deltamethrin e lambda-cyhalothrin foram eficientes no controle de B. germanica, antes da lavagem, na superfície lisa. A eficiência de controle dos inseticidas foi maior na superfície lisa que na superfície rugosa. Após a lavagem, a eficiência diminuiu em ambas as superfícies.
MORTALITY OF BLATTELLA GERMANICA (L.) (BLATTODEA: BLATTELLIDAE) IN RELATION TO THE PERCENTAGE OF EXPOSURE TO PESTICIDES AND TYPE OF SURFACE, BEFORE AND AFTER WASHING
Keywords: German cockroach; urban pest management; urban pest control; barata alemã; manejo de pragas urbanas; tratamento domissanitário